Accounting in Cyprus during the last four decades of British Rule: Post-World War I to independence (1918–1960). (August 2013) - Clarke, Peter; Varnava, Andrekos
Compared to other countries, little has been written about the accounting history of Cyprus. This omission is surprising given the rich history of the island, today a Commonwealth and European Union member, with its own local accountancy body. This article aims to partly fill this vacuum. Despite Cyprus's links to both Greece and Turkey, it was the experience of British rule that significantly influenced the development of accounting practice in Cyprus. Consequently, this article concentrates on the four decades immediately after the First World War until Cypriot independence in 1960, since this is the era in which the most notable developments in accounting practice occurred. This article traces these developments and their significant influences during that period. Like other country studies on the history of accounting, this article argues that the development of accounting evolved over time in response to the contingent political, economic, institutional and social factors, both at domestic and at international level.